An insight into brown/beige adipose tissue whitening, a metabolic complication of obesity with the multifactorial origin - Ziqubu, Khanyisani; Dludla, Phiwayinkosi V.; Mthembu, Sinenhlanhla X. H.; Nkambule, Bongani B.; Mabhida, Sihle E.; Jack, Babalwa U.; Nyambuya, Tawanda M.; Mazibuko-Mbeje, Sithandiwe E. (Frontiers in Endocrinology, 2023)
Brown adipose tissue (BAT), a thermoregulatory organ known to promote energy expenditure, has been extensively studied as a potential avenue to combat obesity. Although BAT is the opposite of white adipose tissue (WAT) which is responsible for energy storage, BAT shares thermogenic capacity with beige adipose tissue that emerges from WAT depots. This is unsurprising as both BAT and beige adipose tissue display a huge difference from WAT in terms of their secretory profile and physiological role. In obesity, the content of BAT and beige adipose tissue declines as these tissues acquire the WAT characteristics via the process called “whitening”. This process has been rarely explored for its implication in obesity, whether it contributes to or exacerbates obesity. Emerging research has demonstrated that BAT/beige adipose tissue whitening is a sophisticated metabolic complication of obesity that is linked to multiple factors. The current review provides clarification on the influence of various factors such as diet, age, genetics, thermoneutrality, and chemical exposure on BAT/beige adipose tissue whitening. Moreover, the defects and mechanisms that underpin the whitening are described. Notably, the BAT/beige adipose tissue whitening can be marked by the accumulation of large unilocular lipid droplets, mitochondrial degeneration, and collapsed thermogenic capacity, by the virtue of mitochondrial dysfunction, devascularization, autophagy, and inflammation.